Designing and Validating the local Model of Entrepreneurship Education in Technical and Vocational Education Centers - Kor, Abdullatif; Kordestani, Fereshteh; Hosseinikhah, Ali; Delgoshai, Yalda (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2021)
Background and Purpose: This research was conducted with the aim of designing and validating the local model of entrepreneurship education in technical and vocational education centers. Method: The purpose of this research is developmental-applied type of mixed studies (qualitative-quantitative). In the qualitative part, the theme analysis method was used to identify and the fuzzy Delphi method was used to summarize the indicators, and in the quantitative part, the descriptive-survey method was used. The statistical population in the qualitative part included experts (university faculty members) in the fields of entrepreneurship, educational management and human resource management, managers of technical and professional centers, entrepreneurship lecturers who reached theoretical saturation with eighteen interviews and in the quantitative part with Cochran’s formula. A total of 384 center managers, part-time and full-time academic staff, and entrepreneurship course instructors were selected as samples. In the qualitative part, 5 dimensions, 16 components and 63 indicators were identified. In the second part, the number of indicators was reduced from 63 indicators to 60 indicators in two rounds with the fuzzy Delphi method. Finally, the validity of the questionnaire was confirmed by the Cvr method. Cronbach’s alpha with a coefficient of 0.868 was a high reliability of this questionnaire. Results: According to the results of the research model, it showed that among the identified factors, the educational dimension with a coefficient of 0.932 has the highest importance and priority in entrepreneurship education, and the economic dimension with a coefficient of 0.755 is the least important and the last priority from the point of view of the employees and teachers of technical and vocational schools has it. Conclusion: Therefore, we come to the conclusion that entrepreneurship is a relatively acquired process, and teachers are considered a key element in promoting and teaching entrepreneurship.